Correlation between Knowledge and Attitude with Malaria Prevention Practices in the Working Area of the Kabawo Public Health Center - Arimaswati; Ninis I. Octasari; Ashaeryanto; Indria Hafizah; Pranita Aritrina (MEDULA: Jurnal Ilmiah Fakultas Kedokteran Universitas Halu Oleo, 2023)
Background: Malaria is still one of the public health problems in Southeast Sulawesi Province. Annual Parasite Incidence (API) in the work area of Kabawo Primary Health Center was 48.90‰ in 2016. Limited public knowledge is an essential determinant of the emergence of malaria and influences community participation in malaria prevention programs. Purpose: This research aims to determine the relationship between knowledge and behavior in malaria prevention practices in the work area of Kabawo Primary Health Center. Methods: This research was an observational analytic design using a cross-sectional approach. The dependent variable in this research was malaria prevention practice, and the independent variable was knowledge and behavior. The research location was in the Kabawo Primary Health Center's working area, with 56 respondents using the total sampling method. Data were obtained by filling out the knowledge questionnaires, behaviors and practices, and interviews. Data analysis used a spearman rank statistical test with a p-value <0.05 and contingency coefficient (r-value). Result: The result of this research of 56 respondents found 22 respondents (39.3%) had good knowledge, good behavior, and good prevention practices, as many as 12 respondents (21.4%) had good knowledge, good behavior, and less of prevention practices, as many as 22 respondents (39,3%) have less knowledge, less behavior and less of prevention practices. Based on the results of the Spearman rank statistical test analysis, it was found that the knowledge and behaviors with malaria prevention practices showed the p-value of 0,000 <0,05 with the value r = 0,647. Conclusion: This research concluded that there was a relationship between knowledge and behaviors to prevention practices in the work area of Kabawo Primary Health Center and had a strong correlation between variables with a positive correlation direction, meaning that the better knowledge and behaviors, the better prevention practices.